MOTIVATION AND AFFECTIVE FACTORS TO LEARN ENGLISH AS SECOND LANGUAGE - Eragamreddy, Nagamurali (Premise: Journal of English Education and Applied Linguistics, 2024)
This study explores the complex interplay between motivation and affective factors, emphasizing these components' critical role in the effectiveness of English as a second language (ESL) learning. Comprehending these processes enables educators to establish conducive situations that foster language acquisition. The study investigates the reasons behind ESL learners, ranging from authentic curiosity about the language and culture to pragmatic professional objectives. It examines how motivation interacts with attitudes, emotions, and anxiety levels during learning. To examine research on affective factors and motivation in ESL learning, using a qualitative research approach, the researcher reviewed the literature and examined academic books and articles about the motivations, challenges, emotional experiences, and cultural backgrounds of ESL learners, making sure to include relevant details and cite all relevant sources by American Psychological Association (APA) guidelines. The results highlight the relationship between affective factors and motivation. Anxiety may impede language acquisition, whereas positive attitudes and internal motivation drive the process. The study emphasizes how crucial it is to have a welcoming classroom that considers cultural diversity and promotes a feeling of community. Policymakers and educators can benefit greatly from the insights this research induces. Educators may customize lessons to suit student requirements and learning styles by recognizing the interaction between affective factors and motivation. This will eventually result in a more positive and practical ESL learning experience for all students.